Existential and bioethical aspects of palliative care in cancer - Langaro, Fabíola (2023)
Severe illness places individuals in direct confrontation with death, an element of the experience of living. A total of 12 interviews were conducted with adults undergoing palliative care in cancer, and investigated by phenomenological analysis, describing the axes of meaning produced in the narratives. Analysis of the ways individuals (re)organize their life projects based on illness and finitude identified three dimensions: spirituality/religiosity; life in the family; relationship with death. The meaning patients attribute to existential trajectories and the relationship established with their life project are essential for treatment adherence and coping with death. Resignifying life, illness and death can relieve suffering and help patients give meaning to the time left. Such questions help us reflect on the bioethical dimension of palliative care and enable planning in this modality of care.